Association of cord blood and maternal lipid profile - Zohra, Noor Fathima S.; Prabhu, Anitha S.; Rao, Smitha B.; Saldanha, Prakash R. M. (International Journal of Contemporary Pediatrics, 2020)
Background: Cardiovascular diseases (CVDs) are the leading cause of mortality and morbidity with dyslipidemia as an important contributing risk factor. Objective of the study was to determine whether there is an association between maternal lipid profile and the cord blood lipid profile of their newborns. Methods: This was a hospital-based Cross-sectional study on 60 mothers and their respective newborns (30 term and 30 preterm) conducted in Yenepoya medical college hospital from August to November 2019. Umbilical cord blood samples from the newborns were collected after birth and the mother’s venous blood was collected in the fasting state (8hrs of fasting) before delivery. The levels of total cholesterol, triglycerides, HDL, LDL and VLDL were determined in mothers and their newborns by an enzymatic colorimetric method. Data obtained was analyzed by the SSPS software 23.0 version and Pearson’s correlation was done. Results: There was a significant correlation between the mean concentration of maternal Triglycerides and the Triglycerides and HDL levels of neonates (p-value <0.05). Conclusions: There was a significant association of cord blood and maternal lipid profile, hence changes in maternal lipid levels might influence the lipid levels in the cord blood of newborns.